2010
DOI: 10.1051/0004-6361/200912726
|View full text |Cite
|
Sign up to set email alerts
|

Infrared properties of the SDSS-maxBCG galaxy clusters

Abstract: Context. The physics of galaxy clusters has proven to be influenced by several processes connected with their galactic component which pollutes the intracluster medium (ICM) with metals, stars and dust. However, it is not clear whether the presence of diffuse dust can play a role in clusters physics since a characterisation of the infrared (IR) properties of galaxy clusters is very challenging and yet to be completely achieved. Aims. In our study we focus on the recent work of Giard et al. (2008, A&A, 490, 547… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
5
16
0
Order By: Relevance
“…The dominant component for both luminosity functions is the ISM dust in spirals, in agreement with the interpretation proposed by Roncarelli et al (2010) that late-type galaxies should dominate the overall dust IR emission in galaxy clusters. We confirm this conclusion through our optically-calibrated model (in the V-band).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The dominant component for both luminosity functions is the ISM dust in spirals, in agreement with the interpretation proposed by Roncarelli et al (2010) that late-type galaxies should dominate the overall dust IR emission in galaxy clusters. We confirm this conclusion through our optically-calibrated model (in the V-band).…”
Section: Resultssupporting
confidence: 90%
“…Their detected emission attributable to dust is not higher than a DtG of 10 −5 , after an X-ray-derived star formation correction. Roncarelli et al (2010) is a follow-up to Giard et al (2008) on a restricted redshift range of 0.1 < z < 0.3 SDSS-maxBCG clusters ), for which they modeled (following the prescriptions presented in Silva et al 1998, according to various morphologies, namely E/S0, Sa, Sb, Sc and starburst) the 60 and 100 µm IRAS band emission of the cluster galaxies, to separate the IR emission from dust in known galaxies from other components such as the ICM dust. Their estimated total galactic emission is dominated by star-forming late-type galaxies, leading to a derived DtG 5 × 10 −5 .…”
mentioning
confidence: 99%
“…(2), we get again a dust mass of 2 × 10 9 M . According to the discussion by Roncarelli et al (2010), the infrared emission at 100 μm from galaxies in clusters is dominated by the emission of late-type spiral galaxies. Those authors estimated a flux of 1904.8 Giard et al (2008) are roughly compatible with their estimations and leave little chance for any component associated to intracluster dust.…”
Section: Methods 2: Infrared Luminosities and Total Dust Contentmentioning
confidence: 97%
“…Those authors obtained a clear statistical detection of emission in the bands at 12, 25, 60, and 100 μm. According to the estimation of IR emission due to the different galaxy populations in cluster member galaxies, Roncarelli et al (2010) concluded that most (if not all) of the signal detected comes from the emission of dust in cluster members. The MIPS (Multiband Imaging Photometer for Spitzer) offered a significant quantitative improvement that has allowed studies of single clusters (Bai et al 2007on Abell 2029and Kitayama et al 2009 on Coma cluster).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of infrared emission cluster by cluster is difficult at millimetre wavelengths, since the emission is faint and confused by the fluctuations of the infrared sky (Galactic thermal dust and CIB). Statistical detections of infrared emission in galaxy clusters have been made by stacking large samples of known clusters (Montier & Giard 2005;Giard et al 2008;Roncarelli et al 2010) in IRAS data (Wheelock et al 1993). The stacking approach has also been shown to be a powerful method for extracting the tSZ signal from microwave data (e.g., Lieu et al 2006;Diego & Partridge 2009).…”
Section: Introductionmentioning
confidence: 99%